THE EXISTENCE OF PEDICAB IN DEVELOPING TOURISM IN MALIOBORO - Santoso, Ihsan Budi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
The objective of this research is to describe â€œthe existence of pedicab in developing tourism in Malioboroâ€ which is viewed from the perception of pedicab driver toward the tourism in Malioboro and the strength and the obstacle of pedicab. Malioboro is one of the tourist objects in the City of Yogyakarta that currently still to place the public transportation non motorized such as pedicab in developing the tourism in Malioboro. Its existence is also one of the tourism activities in the region have made as the beautiful one for tourists. This research is a descriptive qualitative. The data is collected through an observation, an interview and literature review. The result of the research shows that the perception of pedicab driver toward its tourism is good. There is progress of tourism in Malioboro street. Second, it can be viewed from the strengths and the obstacles of pedicab. The strength shows that pedicab is a means of promotion and advertisement of tourism in Malioboro. The pedicab is an icon of Yogyakarta, especially in Malioboro. The obstacle is the existence of competitor in the field. This condition makes the difficulties for the pedicab as non motorized transportation. In economic aspect, this phenomenon will influence the economic life of the pedicab driver. Keywords: perception, tourism and transportation.